Opportunities of developing functional foods - Kmeth, Sándor (Acta Agraria Debreceniensis, 2014)
This study summarizes and compares the definitions and applications of functional foods from the viewpoints of the different societies. Provides an overview of the functionalities of foods based on the scientific approach of today’s Western – including Hungarian – cultures and the traditional Indian approach that dates back to the ancient times. Gives a short description and comparison of the basic concepts and background knowledge of functional foods according to these two worldviews.